Service Quality on Customer Satisfaction and Its Impact on Customer Loyalty at KFC in South and Southeast Asia - Dr. Jocelyn Lee Jia Lin; Dr. Hui Lim Ling; Dr. Gai Sin Liem; Ms. Atiba Batul; Nur Adnin Shazlyana Binti Shamsudin; Nur Afifah Binti Zainal Abidin; Nur Aina Arisya Bt. Mohd. Farid; Nur Alya Umairah Binti Mohd. Shuhaimi; Egananda Kurniawan; Deepjyoti Dutta; Bhavesh K. Hasani (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
Kentucky Fried Chicken (KFC) is the world’s well-known global brand of fast food that has more than 26,000 restaurants in over 150 countries and territories around the world. Due to Its cheapness, quickness, and convenience, it has always become a global favorite meal for many people. However, the quality of services also plays an important role in KFC’s success as they apply customer-oriented services. Their empathy and reliability towards their products and services give many reviews on the internet. Although there are many top brands in the fast-food industry, KFC has succeeded in quickly developing its business as they are constantly expanding throughout the world. Therefore, their success raises an issue of how they maintain their customer’s loyalty. To better understand this research, an online survey has been created to collect the data needed. This survey involves 100 participants from Malaysia, Indonesia, and India through a questionnaire in a Google Form. The quantitative method was used with random sampling. The data were utilized with the regression test, one sample t-test, and f-test. Based on the findings, KFC's service quality has a favorable impact on customer loyalty in each country.